Dark matter inner slope and concentration in galaxies: from the Fornax dwarf to M87. Issue Volume 10:Issue S311(2014) (10th April 2015) - Mamon, G. A.; Chevalier, J.; Romanowsky, A. J.; Wojtak, R.
Abstract: We apply two new state-of-the-art methods that model the distribution of observed tracers in projected phase space to lift the mass / velocity anisotropy (VA) degeneracy and deduce constraints on the mass profiles of galaxies, as well as their VA. We first show how a distribution function based method applied to the satellite kinematics of otherwise isolated SDSS galaxies shows convincing observational evidence of age matching: red galaxies have more concentrated dark matter (DM) halos than blue galaxies of the same stellar or halo mass. Then, applying the MAMPOSSt technique to M87 (traced by its red and blue globular clusters) we find that very cuspy DM is favored, unless we release priors on DM concentration or stellar mass (leading to unconstrained slope). For the Fornax dwarf spheroidal (traced by its metal-rich and metal-poor stars), the inner DM slope is unconstrained, with weak evidence for a core if the stellar mass is fixed. This highlights how priors are crucial for DM modeling. Finally, we find that blue GCs around M87 and metal-rich stars in Fornax have tangential outer VA.